2015
DOI: 10.9775/kvfd.2014.12015
|View full text |Cite
|
Sign up to set email alerts
|

Kefir, Kımız, Süt ve Yoğurt Uygulamasının Fare Dalağında Plazma Hücresi ve Mast Hücrelerinin Dağılımı Üzerine Etkileri

Abstract: The present study was conducted to investigate the effect of kefir, koumiss, milk and yoghurt administration on plasma cells, which synthesize specific antibodies against antigens, and mast cells, which have a role in the regulation of humoral and cellular events, in the mice spleen tissues. Mice (n=30) were divided into 5 groups. As a result of statistical evaluation, live weights of mice in kefir, koumiss, milk and yoghurt groups were found to be increased compared to the control group. When numbers of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the developing world kefir drink increasingly become as popular. Its known that Caucasian origin acidic and midly alcolic fermented milk kefir drink contain benefical microorganisms and can treat some diseases [9] and has an effect on natural immune system it modulates the immune system [30] and also previous studies reported that kefir including many benefical general health properties such as antioxidant features [14,31] . In the study its clearly observed that affiliated to CCl 4 administration severe liver damage was formed but kefir drink significantly reduced pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing world kefir drink increasingly become as popular. Its known that Caucasian origin acidic and midly alcolic fermented milk kefir drink contain benefical microorganisms and can treat some diseases [9] and has an effect on natural immune system it modulates the immune system [30] and also previous studies reported that kefir including many benefical general health properties such as antioxidant features [14,31] . In the study its clearly observed that affiliated to CCl 4 administration severe liver damage was formed but kefir drink significantly reduced pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…All the obtained data was converted to number of somatostatin positive cells per 1 mm 2 unit area [22,23] . Numerical distribution of somatostatin positive cells were observed in six sections chosen from six unit area of Langerhans of each animals.…”
Section: Immunohistochemical Procedures and Statistical Analysismentioning
confidence: 99%